2006
DOI: 10.1002/mrd.20537
|View full text |Cite
|
Sign up to set email alerts
|

In utero exposure to tributyltin alters the expression of e‐cadherin and localization of claudin‐1 in intercellular junctions of the rat ventral prostate

Abstract: Tributyltin (TBT) is an environmental contaminant, exhibiting well-established toxicity to reproductive systems in aquatic organisms. Little information exists regarding the effects of TBT on mammalian reproduction. Cellular junctions are crucial for sperm development and maturation. Intercellular tight junctions are formed by transmembrane proteins such as claudins (Cldns), while the formation of tight junctions involves signaling components of adhering junctions, comprised of cadherins. The objectives of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…This is reflected by the significantly higher ventral prostate weight observed in treated adults when androgen levels are similar to those in control rats. While androgens regulate prostate weights, toxicants such as tributyltin have been reported to alter prostate weights independent of circulating androgens [40]. Indeed, Zhao et al [41] demonstrated androgen-independent growth of prostate cells mediated by glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…This is reflected by the significantly higher ventral prostate weight observed in treated adults when androgen levels are similar to those in control rats. While androgens regulate prostate weights, toxicants such as tributyltin have been reported to alter prostate weights independent of circulating androgens [40]. Indeed, Zhao et al [41] demonstrated androgen-independent growth of prostate cells mediated by glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, E-cadherin and claudin-1 expression levels decreased in a dosedependent response, while claudin-3 and -8 increased in high-dose treatments, suggesting that some compensatory effect among the various claudins present in the ventral prostate. In addition, claudin-1 immunolocalization was shown to be spread throughout the plasma membrane in animals exposed to TBT, rather than restricted to the apical margin of adjacent epithelial cells, as in the control group, suggesting possible changes in the tight junctions function [23].…”
Section: Xenobiotics Acting In Cell Junctions Impairing Prostatic Devmentioning
confidence: 81%
“…In a study with pregnant rats, Barthelemy et al [23] observed a significant dose-dependent decrease in E-cadherin mRNA levels in the ventral prostate of adult rats exposed in utero to increasing doses of TBT (2.5, 10, and 20 mg/kg). G-proteins play an essential role in the signaling process, implicating cell adhesion molecules such as cadherins [23]. Microarray analyses indicated that four Gproteins, Rab16, Rab 14, RaI A and GNAI2, significantly decreased in the TBT-treated rats, indicating a possible imbalance in the process related to establishment and/or maintenance of cell polarity.…”
Section: Xenobiotics Acting In Cell Junctions Impairing Prostatic Devmentioning
confidence: 98%
See 2 more Smart Citations